THE RAINFOREST BOOK - Milner, Charlotte (London : Dorling Kindersley, 2021)
Sweep aside the liana vines, hop over the giant roots of the kapok tree, and follow the sound of the howler monkey as you venture into the tropical rainforest. Find out about some of the amazing animals that live there, learn about the enormous variety of life-giving plants, and discover why the Amazon rainforest is known as the 'lungs' of our Earth.
Protecting the places that are precious.
Keywords: Rain forest ecology -- Juvenile literature; Habitat (Ecology) -- Juvenile literature; Trees -- Juvenile literature; Plants -- Juvenile literature; Illustrated works